Analisis Perilaku Biaya Dalam Hubungannya Dengan Perubahan Volume Kegiatan Perusahaan - Muanas, Muanas; Triandi, Triandi; Rahmi, Salamah (Institut Bisnis dan Informatika Kesatuan, 2015)
The purpose of this study is to classify the cost based on the cost relationship to the volume of the company's activities, into variable costs andfixed costs, as well as determine the role of the cost analysis ofthe company's intemal use. Conducting this study, the authors analyze and classify re-grouped costs into variable costs and fixed costs, and the cost of separating the semi-variable using the least squares method. Moreover, the authors calculate the break-even point, contribution margin and safety margin. Based on data in October, November and December 2013 this study finds that there are some costs that are less precise in the grouping, this can affect the company 's profit. Based on calculations, PT. Syslab increased the profit in every month. Keywords: cost behavior, volume of corporate activity